2018
DOI: 10.1002/jcb.27784
|View full text |Cite
|
Sign up to set email alerts
|

Delphinidin induces antiproliferation and apoptosis of endometrial cells by regulating cytosolic calcium levels and mitochondrial membrane potential depolarization

Abstract: Endometriosis is a benign gynecological disease of women of reproductive ages, wherein endometrial cells grow ectopically, decreasing their quality of life due to chronic pelvic pain and severe dysmenorrhea. Although surgery and hormone therapies are gold standards for treating endometriosis, side effects are common and the recurrence rate is nearly 50%. Recent studies are exploring phytochemicals as pharmacological adjuvants for treating endometriosis. Delphinidin is an anthocyanin with anti‐inflammatory, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Using the same model and cells, the same group showed that delphinidin exerts proapoptotic and antiproliferative effects mediated by MAPK and PI3K/AKT signaling proteins. These effects were accompanied by a decrease in the phosphorylation of ERK1/2, AKT, p70S6K, S6 and an increase in the phosphorylation of p38 MAPK and p90RSK [114]. Delphinidin induced apoptosis in human endometrial cells by decreasing the mitochondrial membrane potential and increasing the [Ca 2+ ] i. Safrole-mediated apoptotic cell death in HSC-3 cells was associated with an increase of cytosolic Ca 2+ levels, a decrease in the mitochondrial membrane potential, and activation of Fas-dependent pathways [115].…”
Section: Targeting Calcium Signaling For Anti-cancer Therapymentioning
confidence: 99%
“…Using the same model and cells, the same group showed that delphinidin exerts proapoptotic and antiproliferative effects mediated by MAPK and PI3K/AKT signaling proteins. These effects were accompanied by a decrease in the phosphorylation of ERK1/2, AKT, p70S6K, S6 and an increase in the phosphorylation of p38 MAPK and p90RSK [114]. Delphinidin induced apoptosis in human endometrial cells by decreasing the mitochondrial membrane potential and increasing the [Ca 2+ ] i. Safrole-mediated apoptotic cell death in HSC-3 cells was associated with an increase of cytosolic Ca 2+ levels, a decrease in the mitochondrial membrane potential, and activation of Fas-dependent pathways [115].…”
Section: Targeting Calcium Signaling For Anti-cancer Therapymentioning
confidence: 99%
“…Finally, naringenin significantly increased apoptosis through generation of ER stress regulatory genes, in particular G1 arrest and DNA damage 153 (GADD153), inositol-requiring protein 1α (IRE1α) and GRP78, and through activation of MAPK signaling and inactivation of PI3K pathway. It is interesting to note that the same group of authors investigated these same biological mechanisms highlighted for chirisin, narigenin for other substances, such as apigenin, delphinidin, luteolin, quercetin, silibinin and myricetin in VK2/E6E7 and End1/E6E7 endometriotic cells lines [ 50 , 55 , 61 , 67 , 68 , 69 ]. All these studies are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 98%
“…A total of 286 studies were initially identified by the search criteria. After applying the selection criteria, a total of 60 trials were included in the systematic review [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be associated with decreased mitochondrial membrane potentials and enhanced cytosolic calcium levels in VK2/E6E7 and End1/E6E7 cells. In addition, Del attenuates the phosphorylation of ERK1/2, AKT, P70S6K, and S6 and enhances the phosphorylation of p38 MAPK and P90RSK . Del treatment has been reported to effectively suppress mechanical unloading-induced muscle weight loss.…”
Section: Additional Discussionmentioning
confidence: 99%